Contested Space of Transborder Fishing in Timor and Arafura Seas - Shiskha Prabawaningtyas (Diponegoro University, 2017)
The continuity of Indonesian transborder fishing activities into Australian Fishing Zone (AFZ) highlights the rooted dispute of maritime border when contested space of boundary shared by local, state and international actor is confronted. Therefore, the prevailing of multilayer perspective of maritime boundary should not be easily neglected. The colonial project in early 19th century in Southeast Asia that initiated the foundation of modern state-formation had challenged the prior-political and economic construction of the region, specifically on the issue of territoriality. The modernization of shipping and fishing activities of which relied on technology and capitals had generated political and economic competitions and later persuaded state’s actors of applying the strategy of the territorialisation of the sea in order to ensure control. Unavoidably, securitization of transborder fishing became preferable solution. Transborder fishings are further subjected into state control relied on territorial sovereignty.This paper examines the transformation of transborder fishing in Timor and Arafura Sea to demonstrated the contested space of which interplayed by local, state and international actor. State regulations had transformed transborder fishing into political space of authority competition relied on territorial sovereignty, while socio-cultural heritage reminds exploited within fluid space of livelihood survival when state function is just absent.